Modified robotic-assisted laparoscopic pyeloplasty in children for ureteropelvic junction obstruction with long proximal ureteral stricture: The “double-flap” technique - Han, Ce; Ma, Lifei; Li, Pin; Wang, Jia’nan; Zhou, Xiaoguang; Tao, Tian; Cao, Hualin; Tao, Yuandong; Yang, Yunjie; Zhao, Yang; Zhu, Weiwei; Guo, Tao; et al. (Frontiers in Pediatrics, 2022)
Objectives: To introduce a new technique of robotic-assisted laparoscopic pyelo- plasty(RALP) for ureteropelvic junction obstruction(UPJO) with long proximal ureteral stricture in children . Methods: Between July 2018 and May 2019, children who underwent modified robotic-assisted laparoscopic pyeloplasty (MRALP) in our center were analyzed retrospectively. Our surgical modifications were mainly about that the pelvis was tailored into “double flaps” and the spatulated ureter was anastomosed with the inferior flap. Demographic, perioperative and postoperative follow-up information were recorded in detail. Results: A total of 13 patients were included in the study. All underwent modified robotic-assisted laparoscopic pyeloplasty without conversion to open surgery. All patients were followed up on the average of 33.5 months, The anterior and posterior diameter of renal pelvis (1.19 ± 0.21) at 6 months after operation was significantly lower than that before operation (3.93 ± 0.79). The split renal function of children before operation (0.37 ± 0.05) was significantly lower than that at 6 months after operation (0.46 ± 0.02) (P < 0.05). At six months after operation, diuretic renography revealed that all the patients have a T1/2 time less than 20 min. The children were generally in good condition during the follow-up period, and there was no restenosis. Conclusions: The modified robotic-assisted laparoscopic pyeloplasty is a safe, viable and effective surgical treatment for children with ureteropelvic junction obstruction combined with long proximal ureteral stricture. The success rate of the operation is high and the children preforming modified surgery recuperate well.